PENGARUH LATIHAN SENAM AEROBIK TERHADAP PENURUNAN KADAR LEMAK TUBUH ANGGOTA SENAM SANGGAR KEBUGARAN MUSLIMAH CENTRE PADANG - Debby Indah (STKIP ROKANIA, 2016)
The purpose of this research was to explain the effect of aerobic exercise on the decreaced the fatty level in the body. The kinds of this research was guasi experiment. It was divided into two groups. Group I exercised 5x times a week and group II 3x times a week. In which bath group members become sample through mathcing.The research population was 63 members of Muslimah Centre Gymn Padang,who are overweight. The sample was taken using volunteer sampling as many as 30 sample. For the instrument, the researcher used skin fold calliper with pretest and posttest to collect the data, which was analysed using descriptive statistics and ttest with lever of significance 0.05 The result showed that aerobic exercise with the frequency of 5x a week had significant effect on the decrease of fatty level with the value of ttest 19.25. Likewise, the aerobic exercise with the frequency of 3x a week also had significant effect with the value of ttest 15.96. The significance between the two freguency is obtained with the value of 5.88, higher than ttable 2.145. In conclusion, a more freguency aerobic exercise (5x times a week) has higher effect on the decrease of fatty level compared to exercise with lower freguency (3x times a week)